We need to be alive to continue the struggle: pandemic and the struggle of Munduruku women - Munduruku, Alessandra Korap; Chaves, Kena Azevedo [UNESP] (Univ Nac Colombia, Sede Amazonia, 2020)
The Munduruku people in the Tapajos River are under intense pressure from large scale projects and economic interests on their territory. This situation is aggravated by the current government and also by the advance of the pandemic that affects indigenous peoples in the Amazon, exposing the vulnerabilities of protection and health policies. The coronavirus is already making victims among the Munduruku, and the people suffer from the loss of chiefs, leaders and family members. Through the Wakoborun Association, Munduruku women have put themselves at the forefront of fighting the pandemic, supporting their relatives. The work that follows is an account of the situation, highlighting the role of women in fighting the virus and the other pressures suffered by the people. The work is built through collaboration between the authors, the reports of the first author, leadership of the people, are organized and edited by the second author, who complements in comments with bibliographical and documentary review. The analyzes were built together, based on shared dialogues and readings of the text.
Keywords: Munduruku; indigenous women; pandemic; Amazon; struggle for territory